Central line-associated bloodstream infection trend in Brazilian adult intensive care units: an ecological study - Alexsandra Gomes Resende de Souza da Silva; Sergiane Bisinoto Alves; Elisângela Eurípedes Resende Guimarães; Jessyca Rodrigues Braga; Heliny Carneiro Cunha Neves; Silvana de Lima Vieira dos Santos; Maria Auxiliadora Carmo Moreira (Journal of Infection in Developing Countries)
Introduction: Central line-associated bloodstream infections are the second most frequent infection in intensive care units. It represents an adverse event of significant magnitude, thus threatening the patient safety. The aim of this study was to analyze the historical trend of central line-associated bloodstream infections in patients in intensive care units, the rate of infection, central venous catheter utilization ratio, type of pathogen and their antimicrobial resistance pattern.